2011
DOI: 10.1002/ejsp.867
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup anxiety from the self and other: Evidence from self‐report, physiological effects, and real interactions

Abstract: Intergroup anxiety has become important in understanding the success or failure of intergroup contact. In this paper, we suggest that intergroup anxiety is made up from two constructs: self-anxiety (anxiety over thinking or doing something that is prejudiced) and other-anxiety (anxiety that the other might do something to you). Over four studies, we show how these two dimensions have different correlates and independently predict psychophysiological reactivity to an intergroup interaction. Other-anxiety was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 68 publications
(116 reference statements)
3
37
0
Order By: Relevance
“…How certain can we be that they measure what we intend them to measure? To this end, Greenland, Xenias, and Maio (2012) developed a measure of intergroup anxiety and used an abridged version of Stephan and Stephan's (1985) scale to help demonstrate convergent validity (Study 2). Greenland et al (2012, Study 3) then demonstrated that their intergroup anxiety scale correlated with physiological responses that are associated with the experience of anxiety.…”
Section: Results and Commentsmentioning
confidence: 99%
“…How certain can we be that they measure what we intend them to measure? To this end, Greenland, Xenias, and Maio (2012) developed a measure of intergroup anxiety and used an abridged version of Stephan and Stephan's (1985) scale to help demonstrate convergent validity (Study 2). Greenland et al (2012, Study 3) then demonstrated that their intergroup anxiety scale correlated with physiological responses that are associated with the experience of anxiety.…”
Section: Results and Commentsmentioning
confidence: 99%
“…This could lead to an overall null or weak effect of anxiety on quality of contact. In line with this argument, Greenland, Xenias, and Maio () showed that intergroup anxiety, typically measured as a single variable, is actually made up from two underlying constructs: other‐anxiety (anxiety that the other might be difficult, awkward, or actively hostile) and self‐anxiety (anxiety over thinking or doing something that is prejudiced). Other‐anxiety is associated with more negative attitudes, negative affect, and less contact, which most likely are associated with negative behaviors such as avoidance or antagonism, as typically expected from the intergroup anxiety literature.…”
Section: Resultsmentioning
confidence: 99%
“…These included the 20-item Self Other Intergroup Anxiety Scale (SOIAS; Greenland et al, 2012) which distinguishes self-anxiety (anxiety over thinking or doing something that is prejudiced; e.g., “I am anxious about doing something that makes me look prejudiced;” α = 0.87) and other-anxiety (anxiety that the other person might do something to you; e.g., “I am anxious about him being difficult;” α = 0.91), and Plant and Devine's (2003) generic, 4-item, intergroup anxiety measure (e.g., “I will feel uncomfortable when interacting with him;” α = 0.85). The response scale for these measures was anchored at −3 (“Strongly disagree”) and +3 (“Strongly agree”).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, there is some correlational (but no causal) data that links approach/avoidance to self- and other-anxiety. Greenland et al (Study 4, 2012) reported a positive relation between approach and self-anxiety and a negative relation between approach and other-anxiety. However, there was also a positive relation between self-anxiety and avoidance (which was interpreted by the authors as indicative of freezing; see also Vorauer and Turpie, 2004; Trawalter et al, 2009).…”
Section: Intergroup Contact As An Intergroup Interventionmentioning
confidence: 98%
See 1 more Smart Citation